Inference Analysis in Netizen Opinions on the Issue of Owners of Skincare Money Laundry - Clementina Vincencia Kandam; Kharisma Shinta (Universitas Sebelas Maret, 2024)
The research entitled Inference Analysis in Netizen Opinions on the Tik Tok Shop Closing Issue aims to describe Yohan Agustin's YouTube channel and several Tik Tok content creators regarding the issue of Money Laundry Owner Skincare. The research approach applied is descriptive qualitative which analyzes research findings in the form of words. The data was analyzed through the stages of data reduction, data presentation, inference and verification based on the results of non-participant observations from the videos. The technique used in research is the listening and note-taking technique. The results of the research show that research results in the form of data obtained from the types of inference that appear in video speech on the YouTube and Tik Tok platforms regarding the issue of Money Laundry Owner Skincare, namely Cultural Discourse Inference 2 findings, Economic Discourse Inference 5 findings, Legal Discourse Inference 1 finding and Discourse Inference Social 1 finding in the form of data obtained from the type of inference that appears in video speech on the YouTube and TikTok platforms regarding the Money Laundry Owner Skincare Issue, namely Cultural Discourse Inference 2 findings, Economic Discourse Inference 5 findings, Legal Discourse Inference 1 finding and Social Discourse Inference 1.